Combining Digital Image Correlation and Acoustic Emission for Monitoring of the Strain Distribution until Yielding during Compression of Bovine Cancellous Bone - Tsirigotis, Athanasios; Deligianni, Despoina D. (Frontiers in Materials, 2017)
In this work, the surface heterogeneity in mechanical compressive strain of cancellous bone was investigated with digital image correlation (DIC). Moreover, the onset and progression of failure was studied by acoustic emission (AE). Cubic cancellous bone specimens, with side of 15 mm, were obtained from bovine femur and kept frozen at -20ºC until testing. Specimen strain was analyzed by measuring the change of distance between the platens (crosshead) and via an optical method, by following the strain evolution with a camera. Simultaneously, AE monitoring was performed. The experiments showed that compressive Young’s modulus determined by crosshead strain is underestimated at 23% in comparison to optically determined strain. However, surface strain fields defined by DIC displayed steep strain gradients, which can be attributed to cancellous bone porosity and inhomogeneity. The cumulative number of events for the total AE activity recorded from the sensors showed that the activity started at a mean load level of 36% of the maximum load and indicated the initiation of micro-cracking phenomena. Further experiments, determining 3D strain with μCT apart from surface strain, are necessary to clarify the issue of strain inhomogeneity in cancellous bone.